A New Era of Protection Against Disability Discrimination? The ADA Amendments Act of 2008 and “Regarded As” Disabled - Bradbury, Mark D.; Jacobson, Willow S. (Review of public personnel administration, 2013)
Several U.S. Supreme Court rulings have substantially narrowed the coverage of the Americans with Disabilities Act (ADA) since its passage in 1990. Congress amended the ADA in 2008 to restore the original congressional intent of providing broad coverage for people with disabilities. This article seeks to determine whether the 2008 amendments are a mere technical adjustment of the ADA, or constitute significant legislation in their own right. A review of existing law, resulting regulations, and federal cases reveals that the amendments may promise much but deliver more of the same. Nevertheless, employers are well-advised to renew their efforts to cooperate with applicants and employees with disabilities, if for no other reason than to avoid a costly lawsuit that employers are perhaps now more likely to lose.